(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Melnik O. S. Introduction of the controlled from distance course as means of upgrading of education is in professional preparation of future specialists In the article expediency of introduction of the controlled from distance education is presented in the context of preparation of engineers-technologists and teachers of vocational educational establishments. On the example of development of the educational and methodical providing of discipline of «WEB- technologies and WEB-design» advantages over of the use of environment of the controlled from distance studies of Moodle are brought.